Four-dimensional (4D) bioprinting: a systematic scoping review of stimuli-responsive constructs for applications in tissue engineering and drug delivery - Moghaddasi, Mohammad; Oktay, Busra; Bingol, Ayse Betul; Yanikoglu, Reyhan; Ciftci, Fatih; Ustundag, Cem Bulent (SPRINGERNATURE, 2025)
Four-dimensional (4D) bioprinting integrates with stimuli-responsive biomaterials to create dynamic constructs capable of adapting their shape, properties, or bioactivity in response to specific cues. This systematic review, conducted in accordance with established systematic review guidelines, examines 77 studies sourced from PubMed, Scopus, Web of Science, and bioRxiv. Extrusion-based bioprinting is predominant (approximate to 80%), with fused deposition modeling, stereolithography, and inkjet methods also employed. Physical stimuli, including temperature, humidity, and mechanical forces, are the most commonly utilized alongside less frequently seen chemical and biological cues. Applications in tissue engineering focus on cartilage, bone, neural, vascular, muscle, and soft-tissue regeneration, where programmable constructs show improved tissue morphogenesis. In drug delivery and disease-modeling, reactive oxygen species-, pH-, enzyme-, and temperature-triggered systems facilitate the targeted release of growth factors, genes, and chemo-/immunotherapeutics. Moreover, most of the studies employing shape-morphing and shape memory hydrogels focus on broader biomedical applications. These findings collectively indicate a developing field with the potential to advance next-generation tissue engineering therapies and drug-release systems.
Keywords: Bioprinting; Bioink; Drug delivery; 4D; Stimuli-responsive; Tissue engineering; HYDROGEL; BIOFABRICATION; SCAFFOLDS; REPAIR; Engineering; Materials Science